The effect of temperature on co-pyrolysis of empty fruit bunch and used palm cooking oil for hydrocarbon fuel production - Balasundram, Vekes; Norhuda, Abdul Manaf; Tamunaidu, Pramila; Norazana, Ibrahim; Ruzinah, Isha; Pham, Le Kim Hoang (Penerbit Universiti Teknologi Malaysia, 2025)
This research holds substantial significance in the context of renewable energy and waste management. By investigating the co-pyrolysis of empty fruit bunch (EFB) and used palm cooking oil (UPCO), the study seeks to convert biomass waste into valuable hydrocarbon fuels, thereby addressing environmental concerns associated with waste disposal. Thus, the main goal of this research is to investigate the influence of temperature on the co-pyrolysis of empty fruit bunch (EFB) and used palm cooking oil (UPCO) into hydrocarbon fuel via a fixed-bed reactor. The EFB to UPCO mass ratio was fixed at 1:1, and the temperature varied from 400 to 700°C at 50°C intervals. The generated pyrolysis oil at each temperature was analysed via Gas Chromatography/Mass Spectrometer for organic compositions. Pyrolysis of EFB also was investigated at 500°C for comparison purposes. The results show that adding UPCO increased the pyrolysis yield at all investigated temperatures compared to pyrolysis of EFB only, with the highest pyrolysis oil yield achieved at 600°C (44.4%). The hydrocarbon yield was also significantly influenced by UPCO with varying temperature conditions. The highest hydrocarbon yield of 64.9% was achieved at 650°C followed in descending order as follows: 700°C (63.7%) > 600 °C (48.3%), 550 °C (45.5%), 400°C (4.1%), 500°C (3.1%), 450°C (2.4%) and EFB at 500°C (0%). In pyrolysis oil, oxygenated compounds such as phenols, ketones, aldehydes, acids, furans, esters, and ethers decreased significantly by 45.5 to 64.9% from 550 °C to 700 °C.